Anti-viral activity evaluation of selected medicinal plants of Nigeria against measles virus (2015)
This study was carried out as a preliminary investigation into selected medicinal plants of Nigeria with the aim of discovering and developing a drug with anti-measles virus activity as an alternative measure in disease control. Ten parts of seven plants (Diospyros barteri leaf, Xylopia aethiopica leaf and stem bark, Picralima nitida stem, Cajanus cajan, Argemone Mexicana, Morinda lucida, Uvaria chamae leaf, stem and root bark) were dried, powdered and extracted by cold maceration using absolute methanol, and maximum non-toxic dose (MNTD) of each extract to Vero cell was determined. The cytotoxic activity and ability of extracts to inhibit viral-induced cytopathic effect (CPE) in tissue culture were evaluated three days post-inoculation and incubation, by 3-(4,5- Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) colorimetric assay. Cytotoxic concentration at 50% (CC50) and inhibitory concentration at 50% (IC50) were determined using graphpad prism, and selective index (SI) was calculated as ratio of CC50 to IC50. Out of the ten plant extracts screened, Xylopia aethiopica leaf extract with IC50 of 1.248 μg/mL, Uvaria chamae root and stem bark extracts with IC50 1.216 μg/mL and 3.281 μg/mL, respectively demonstrated significant in vitro anti-measles virus activity. Bioassay-guided fractionation and further screening of active extracts showed activity to reside in the hexane and dichloromethane fractions of X. aethiopica leaf and U. chamae root and stem barks. These results suggest that these two plants could possibly lead to anti-measles virus drug discovery and development.